1983
DOI: 10.1126/science.221.4613.850
|View full text |Cite
|
Sign up to set email alerts
|

Direct Embryogenesis from Mesophyll Cells of Orchardgrass

Abstract: Segments taken from the basal 15 to 20 millimeters of the two innermost leaves of an orchardgrass (Dactylis glomerata L.) genotype produced somatic (nonzygotic) embryos directly from mesophyll cells without an intervening callus when cultured on an agar medium with 30 micromolar 3,6-dichloro-o-anisic acid (dicamba). This demonstration of high-frequency embryogenesis from mesophyll cells in Gramineae is strong evidence for totipotency of the cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0
1

Year Published

1985
1985
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(54 citation statements)
references
References 7 publications
3
49
0
1
Order By: Relevance
“…This is not the first report of direct leaf cell transformation in a monocot; transgenic events have been recovered after transformation of leaf cells in orchardgrass (Denchev et al, 1997). However, before performing these transformation experiments, these researchers selected accessions of orchardgrass that exhibited an atypically high level of somatic embryogenesis when leaf tissue was exposed to exogenous auxin (Conger et al, 1983). More recently, it has been reported that Agrobacterium-mediated transformation directly into young sugarcane leaf tissue has been accomplished (Eldessoky et al, 2011), but again in a species in which somatic embryogenesis from leaf cells in response to auxin has been well established (Lakshmanan et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…This is not the first report of direct leaf cell transformation in a monocot; transgenic events have been recovered after transformation of leaf cells in orchardgrass (Denchev et al, 1997). However, before performing these transformation experiments, these researchers selected accessions of orchardgrass that exhibited an atypically high level of somatic embryogenesis when leaf tissue was exposed to exogenous auxin (Conger et al, 1983). More recently, it has been reported that Agrobacterium-mediated transformation directly into young sugarcane leaf tissue has been accomplished (Eldessoky et al, 2011), but again in a species in which somatic embryogenesis from leaf cells in response to auxin has been well established (Lakshmanan et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Genotypes ofDactylis glomerata L. used in this study included two clones (designated Ela and Elb) of one that exhibited a very high capacity for somatic embryogenesis (4,8) and two (designated NEi and NE2) which exhibited no capacity to produce somatic embryos. Tillers were collected from mature plants grown in an environmentally controlled chamber with a 12 h day/night cycle at 220/1 5C.…”
Section: Methodsmentioning
confidence: 99%
“…For the tissue culture experiments, basal sections of the two innermost leaves were split lengthwise along the midvein and surface sterilized as previously described (4 (14) and is expected since IAA is synthesized in highly meristematic regions, e.g., basal portions of grass leaves, and is transported basipetally. Although IAA concentration is positively correlated with the gradient response for somatic embryogenesis, it does not appear to be related to genotype differences in orchardgrass.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other strong auxins such as dicamba, picloram and or combination of these auxins have been used as alternatives (Conger et al 1983, Lührs and Lörz 1987, Przetakiewicz et al 2003). Most studies develop induction and regeneration systems for the model genotype Golden Promise which has high regeneration efficiency, but is agronomically obsolete (Wan andLemaux 1994, Tingay et al 1997) or for genotypes grown in Canada, U.S., Spain (Baillie et al 1993, Castillo et al 1998, Chant et al 2003.…”
mentioning
confidence: 99%